Aqueous Self‐Assembly and Cation Selectivity of Cobaltabisdicarbollide Dianionic Dumbbells. Issue 22 (15th April 2014) - Tarrés, Màrius; Viñas, Clara; González‐Cardoso, Patricia; Hänninen, Mikko M.; Sillanpää, Reijo; Ďorďovič, Vladimír; Uchman, Mariusz; Teixidor, Francesc; Matějíček, Pavel
Abstract The anion [3, 3′‐Co(C2B9H11)2]− ([COSAN]−) produces aggregates in water. These aggregates are interpreted to be the result of CH⋅⋅⋅HB interactions. It is possible to generate aggregates even after the incorporation of additional functional groups into the [COSAN]− units. The approach is to join two [COSAN]− anions by a linker that can adapt itself to act as a crown ether. The linker has been chosen to have six oxygen atoms, which is the ideal number for K+ selectivity in crown ethers. The linker binds the alkaline metal ions with different affinities; thus showing a distinct degree of selectivity. The highest affinity is shown towards K+ from a mixture containing Li+, Na+, K+, Rb+ and Cs+; this can be indicative of pseudo‐crown ether performance of the dumbbell. One interesting possibility is that the [COSAN]− anions at the two ends of the linker can act as a hook‐and‐loop fastener to close the ring. This facet is intriguing and deserves further consideration for possible applications. The distinct affinity towards alkaline metal ions is corroborated by solubility studies and isothermal calorimetry thermograms. Furthermore, cryoTEM micrographs, along with light scattering results, reveal the existence of small self‐assemblies and compact nanostructures ranging from spheres to single‐/multi‐layer vesicles in aqueous solutions. The studies reported herein show that these dumbbells can have different appearances, either as molecules or aggregates, in water or lipophilic phases; this offers a distinct model as drug carriers.